Role of Bioactive Green Synthesized Nanoparticles in Various Diseases - Barik, Sushanta Kumar; Sewalikar, Akshata; Vijay, Mulay Manjushree; Kulkarni, Smita Sitaram; Harke, Sanjay N; Khemnar, Annasaheb S; Deshmukh, Ashish S.; Dhoble, Sanjay J; Guhe, Sadanand Y (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Nanoparticles (NPs) are transforming agents in biotechnology. The current strategies for diagnostics, targeted drug delivery and therapy may be offered through this transformational agent. The green synthesis of NPs, which may include those obtained from plant extracts, thereby outlining a sustainable and biocompatible approach to nanobiotechnology. This green synthesis method is much less harmful than chemical processes in the aspect of toxicity. It also makes the nanoparticle much more biocompatible and suitable for medical applications. Gold NPs are among the most prominent examples to date and have the significant contributions in the realms of biosensing technologies: enabling early detection of infectious diseases and offering novel pathways for cancer therapy. From green synthesis, the gold NPs possess physicochemical properties that allow them to be a functionalized target delivery system, enhancing therapy efficacy while reducing the onset of side effects. Leverage the bioactive compounds found in plants to understand how such NPs may enhance the diagnosis accuracy and the effectiveness of the therapeutic approaches. Integrating sustainability in biotechnology applications has great potential by way of advancing personalized medicine in the face of environmental sustainability within the field.